A pilot mixed‐methods randomized controlled trial of verbal versus electronic screening for adverse social determinants of health - Wendy Macias‐Konstantopoulos; Gia Ciccolo; Alona Muzikansky; Margaret Samuels‐Kalow (Journal of the American College of Emergency Physicians Open)
Abstract Objectives Examining the social risks that influence the health of patients accessing emergency care can inform future efforts to improve health outcomes. The optimal modality for screening in the emergency department (ED) has not yet been identified. We conducted a mixed methods evaluation of the impact of screening modality on patient satisfaction with the screening process. Methods Patients were enrolled at a large urban academic ED and randomized to verbal versus electronic modalities following informed consent. Participants completed a short demographic survey, a brief validated health literacy test, and a social need and risk screening tool. Participants were purposively sampled to complete qualitative interviews balanced across 4 groups defined by health literacy scores (high vs limited) and screening modality. Quantitative outcomes included screening results and satisfaction with the screening process; qualitative questions focused on experience with the screening process, barriers, and facilitators to screening. Results Of 554 patients assessed, 236 were randomized (115 verbal, 121 electronic). Participants were 23% Hispanic, 6% non‐Hispanic Black, 58% non‐Hispanic White, 38% publicly insured, and 57% privately insured. Two‐thirds (67%) identified social needs and risks and the majority (81%) reported satisfaction with the screening. Screening modality was not associated with satisfaction with screening process after adjustment for language, health literacy, and social risk (adjusted odds ratio, 0.74; 95% confidence interval, 0.32, 1.71). Conclusion Screening modality was not associated with overall satisfaction with screening process. Future strategies can consider the advantage of multimodal screening options, including the use of electronic tools to streamline screening and expand scalability and sustainability.